Desempenho térmico de alvenarias: uma alternativa com o uso de blocos EVA - Gomes, Emmily Gersica Santos (2015)
During the manufacture of footwear, are generated various types of waste, including the Ethylene Vinyl Acetat (EVA), as inevitable patchwork of expanded boards of the material to obtain the shoe formats. An alternative to an appropriate destination of EVA waste is its use in the manufacture of blocks produced with lightweight concrete. The issue addressed in this study is related to the thermal gains made by vertical sealing and thermal comfort of built environments. The environments that do not have the appropriate type of masonry to its climate generate thermal comfort problems due to loss, or excessive heat gain, what happens in regions with predominantly hot dry weather wet hot, as is the case of Northeast Brazil. Considering the thermal discomfort of environments due to misuse elements appropriate in the walls of buildings, as well as the problem of disposal of waste EVA, this work is to extend the characterization of the thermal performance of the blocks composed of EVA. Therefore, we sought to analyze compared samples developed from EVA blocks with other components. The study was done from the development of miniature single skin and double samples (made of EVA blocks, ceramic bricks and concrete blocks), which were tested in a thermal chamber composed of two rooms, a heated and another cooled, separated by an insulating partition in which the sample was inserted. The instrumentation was performed with the use of thermocouples installed in the walls and surfaces of the mini black globe thermometers in the chamber environment. From the experimental characterization of thermophysical properties such as thermal conductivity and density of the EVA blocks of various parameters calculations were performed as set out in NBR 15220-2 (ABNT, 2005b) and calculations to obtain the heat transfer rate of samples. The results demonstrate the efficiency of the insulation block with the highest percentage of waste and the various samples using proposed block can meet EVA hot and wet/dry climate requirements.